Prisons in Malaysia: the law & regulations regarding its condition / Aimy Nordin and Zarina Hanim Ismail - Ismail, Zarina Hanim; Nordin, Aimy (2007)
The last two semesters had been dedicated to conduct a research based on prison conditions in Malaysia. The research was done with the objective to find out the sufficiency of the existing law on the treatment provided for the prisoners and also the prison conditions. The issue whether the existing law is being implemented properly was also been taken into consideration. We also wanted to investigate whether the law was made in accordance with the international principles made by United Nations. The issues that were being highlighted by the SUHAKAM and media are our main resources of information since SUHAKAM is the main medium as the issues obtained were by visiting the prisons in Malaysia. All the issues were then looked into from the perspective of the Prison Regulations 2000 and also Standard Minimum Rules for the Treatment of Prisoners. We conducted interview session with experts that deal with the issue of prison conditions and prisoners treatment. The outcomes of this interview was as we expected. We benefited a lot from the interview since most of the recommendations were relevant for the purpose of this research. Our research was also based on the literatures written by authors specializing in this area and also materials we obtained online.